1996
DOI: 10.1016/0029-7844(96)00054-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Once-Daily and 8-Hour Gentamicin Dosing in the Treatment of Postpartum Endometritis

Abstract: In patients with postpartum endometritis, once-daily gentamicin dosing provides consistently high peak serum levels of gentamicin, requires less nurse tasking time, costs less, and is as effective as the 8-hour dosing regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…8 The numerous physiologic changes that occur during the postpartum period may cause wide fluctuations in the pharmacokinetic parameters. This may explain the differences in elimination rate constant, volume of distribution, and half life between our data and those reported recently by Del Priore et al 9 An additional factor that may reflect a higher half life is that our laboratory could not detect gentamicin levels less than 0.3 mg/L, the trough value used to calculate the half life. Higher trough levels lengthen the half life.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…8 The numerous physiologic changes that occur during the postpartum period may cause wide fluctuations in the pharmacokinetic parameters. This may explain the differences in elimination rate constant, volume of distribution, and half life between our data and those reported recently by Del Priore et al 9 An additional factor that may reflect a higher half life is that our laboratory could not detect gentamicin levels less than 0.3 mg/L, the trough value used to calculate the half life. Higher trough levels lengthen the half life.…”
Section: Discussioncontrasting
confidence: 69%
“…The results of this study support the conclusions of two reports of once-daily gentamicin in the treatment of puerperal uterine infections. 9,10 Oncedaily dosing of gentamicin for the treatment of postpartum endometritis is efficacious and costeffective, and it appears that this regimen is not associated with a high incidence of nephrotoxicity or ototoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…14 Substantial cost savings were similarly noted in the studies by Del Priore et al and Mitra et al 15,16 …”
Section: Costmentioning
confidence: 61%
“…Clinical efficacy of 15 Mitra et al reported on once-daily gentamicin with twicedaily clindamycin versus gentamicin and clindamycin each administered three times a day for puerperal endometritis. The less-frequent dosing schedule was associated with similar outcomes to those with conventional dosing.…”
Section: Once-daily Gentamicin Wiesenfeld and Heinementioning
confidence: 98%
“…9 In addition to convenience, advantages of daily gentamicin include decreased nephrotoxicity in a nonobstetric population, 10 cost, 7,11-13 and need for dosage adjustments. 11 Daily gentamicin has been shown to be safe and at least as effective as 8-hour dosing among postpartum women with endometritis, 7,11,13 neonates, 14 and patients with severe wound infections. 15 In a meta-analysis of daily compared with 8-hour gentamicin for multiple treatment indications, efficacy was equal, there were no differences in ototoxicity, and patients receiving daily gentamicin had less nephrotoxicity.…”
mentioning
confidence: 99%